Study of respiratory complications and outcome in meconium stained deliveries - Shukla, Omprakash S.; S. T., Swapna (International Journal of Contemporary Pediatrics, 2019)
Background: To study the development of respiratory complications in the form of meconium aspiration syndrome (MAS), persistent pulmonary hypertension of newborn (PPHN), pulmonary hemorrhage and pneumothorax in neonates born through meconium stained liquor. Methods: It was a prospective study conducted during the period of February to October 2018. All live babies associated with meconium stained liquor were included. Results: Total 606 neonates with meconium stained amniotic fluid (MSAF) were enrolled. Chance of meconium passage was more after 37wk of gestation, in birth weight >2.5 kg and in AGA babies. The rate of LSCS was higher in MSAF group. MAS developed in 28% cases, out of which 42.9% expired. PPHN developed in 6.9% cases, out of which 80% expired. 100% mortality was there in babies with pulmonary hemorrhage. Apgar scores <7 is significantly associated with the development of respiratory complications. 22.8% of vigorous babies and all non-vigorous babies developed respiratory complications showing statistical significance with P-value of <0.00001. Mortality in MSAF was 12%. All babies who expired had severe meconium aspiration syndrome. 83.9% of the patients stayed for <7 days in the hospital. All of the expiry except one occurred within 7 days of life due to development of respiratory complications. Conclusions: MSAF is associated with the development of respiratory complications and mortality in neonates. Non-vigorous babies and the babies with Apgar scores <7 at birth are more prone to developing respiratory complications. Most of the MSAF babies were discharged and mortality was more in patients with respiratory complications.